ISBAT WAKAF SEBAGAI UPAYA PERLINDUNGAN HUKUM TANAH WAKAF YANG BELUM BERSERTIFIKAT - Susanto, Heru (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Wakaf disputes are found in many places in Indonesia. One of the reasons is that there are many wakaf land that has not been registered (certified) to the authorized official. So it caused that the wakaf land still do not have certainty and the protection of clear law. This issue encourages legal experts to provide solutions to uncertified wakaf land. The solution to provide protection for the wakaf land is the emergence of isbat wakaf as a solution to solve the problems of wakaf land that has not been certified. Isbat wakaf aims to provide law protection of wakaf land, justifying previous law acts such as waqif, nadzir, and managers, and used as evidence in the certification of waqf objects, giving full advocacy to the disputed waqf land or legally problematic. Isbat wakaf is the authority of the Religious Court, this is based on Law no. 14 of 1970 amended by Law no. 4 of 2004 on Judicial Power and Law no. 3 of 2006 on Amendment to Law no. 7 of 1989 on Religious Courts. In Law no. 14 of 1970 amended by Law no. 4 of 2004 on Judicial Power is set forth in Article 2, paragraphs 1 and 2, and Law no. 3 of 2006 on Religious Courts Article 49